(untitled) - Studenmund, A. H. (Harlow, England, 2017)
The Seventh Edition is appropriate for all levels: beginner econometric readers, regression users seeking a refresher, and experienced practitioners who want a convenient reference. Praised as one of the most important texts in the last 30 years, the book retains its clarity and practicality in previous editions with a number of substantial improvements throughout.
Keywords: Kinh tế lượng,Econometrics